Sustainable Awareness About Climate Change on Elementary School Pupils’ Perspective: What Wonderful Finding! - Cucun Sutinah; Ari Widodo; Muslim Muslim; Ernawulan Syaodih (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractClimate change is a serious issue that has become a global problem, so it needs to be responded to and handled immediately. This study aims to obtain an overview of elementary school students' ongoing awareness of climate change. Sustainable awareness is the basis for someone to change their behavior in controlling climate change. This type of research is ex post facto with descriptive quantitative methods used in this study. The instrument for exploring sustainable awareness data is a questionnaire containing 27 statement items that integrate aspects of knowledge, attitudes, and behavior, with environmental, social, and economic dimensions. The questionnaire uses a Likert scale of 1-4, with the choices of strongly agree, agree, disagree and strongly disagree. Respondents were 467 grade 4 elementary school students in the city of Bandung, Indonesia. The questionnaire was filled out online via the Google form within one week. The data obtained was processed and analyzed descriptively quantitatively by calculating the average and percentage of each item, dimensions and aspects of sustainable awareness. The study results revealed that students have a high awareness of sustainability, especially regarding knowledge and environmental dimensions. The findings have implications for introducing students to other aspects and dimensions of sustainable awareness regarding climate change at the elementary school level.Keywords: sustainable awareness, climate change, elementary school students.AbstrakPerubahan iklim merupakan isu serius yang menjadi permasalahan global sehingga perlu direspon untuk segera ditangani. Penelitian ini bertujuan untuk memperoleh gambaran mengenai kesadaran berkelanjutan siswa sekolah dasar akan perubahan iklim. Kesadaran berkelanjutan menjadi dasar untuk seseorang mengubah perilakunya dalam mengendalikan perubahan iklim. Jenis penelitian ex post facto dengan metode kuantitatif deskriptif digunakan dalam penelitian ini. Instrumen untuk menggali data kesadaran berkelanjutan berupa angket yang berisi 27 item pernyataan yang merupakan integrasi aspek pengetahuan, sikap, dan perilaku, dengan dimensi lingkungan, sosial, dan ekonomi. Angket menggunakan skala Likert 1-4, dengan pilihan sangat setuju, setuju, tidak setuju, dan sangat tidak setuju. Responden adalah 467 siswa kelas 4 sekolah dasar di Kota Bandung, Indonesia. Pengisian angket dilaksanakan secara daring melalui google form dalam kurun waktu satu minggu. Data yang diperoleh diolah dan dianalisis secara kuantitatif deskritptif dengan menghitung rata-rata dan persentase setiap item, dimensi, dan aspek kesadaran berkelanjutan. Hasil penelitian mengungkap bahwa siswa memiliki kesadaran berkelanjutan yang tinggi, terutama pada aspek pengetahuan dan dimensi lingkungan. Temuan berimplikasi pada pentingnya mengenalkan siswa pada aspek dan dimensi lainnya dalam konsep kesadaran berkelanjutan terkait perubahan iklim pada jenjang sekolah dasar.Kata kunci: kesadaran berkelanjutan, perubahan iklim, siswa sekolah dasar.